Effect of regular post-exercise cooling on muscle aerobic adaptations to endurance training - Ihsan, M.; Watson, G.; Hui, C. C.; Govus, A.; Pham, T.; Hickey, A.; Markworth, J.; Cameron Smith, D.; Abbiss, C. R. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Cold water immersion (CWI) is a popular technique used to enhance post-exercise recovery (Ihsan et al. 2013). Recently, it was shown that a single CWI intervention enhanced the post-exercise mRNA expression of PGC-1á (Ihsan et al. 2014), a master regulator of muscle oxidative adaptations to endurance training. However, effect of regular CWI interventions on longer term oxidative adaptations to training are yet to be elucidated. The purpose of this study was to investigate the effect of repeated post-exercise CWI on muscle aerobic adaptations to endurance training. Methods: Ten males performed 3 sessions/week of endurance training for 4 weeks. Following each session, subjects immersed one leg in a cold water bath (10°C; CWI) to the level of their gluteal fold for 15 min while the contralateral leg served as control (CON). Prior to, and following the training intervention, subjects performed a graded running test to exhaustion to determine their maximal oxygen uptake (VO2max) and aerobic speed (MAS). Muscle biopsies were obtained from vastus laterallis of both CON and CWI legs prior to training and 48 h following the last training session and analysed for markers associated with aerobic adaptations. Significance was accepted at p<0.05 Results VO2max was improved by 5.4% and MAS was improved by 6.4% following training. Repeated CWI resulted in higher content of phosphorylated AMPK, phosphorylated ACC and the protein expression of respiratory chain complex 3 when compared with CON. However, no training effects were observed in the protein expressions of PGC-1á and respiratory chain complexes 1, 2, 4 and 5. Additionally, no training effects were observed in the enzyme activities of citrate synthase, succinate dehydrogenase and carnitine palmitoyltransferase. Discussion This is the first study to demonstrate enhanced AMPK activity following regular post-training CWI treatment. However, its effect on mitochondrial biogenesis is unclear, as only complex 3 protein expression was significantly enhanced in the CWI leg. While further research is needed to elucidate the mechanisms by which postexercise CWI activates AMPK, it is plausible that cold induced adrenergic activation was responsible for the increased AMPK activity (Tadaishi et al. 2011).